Size Structure and Growth of Snail Terebralia palustris in Mangrove Ecosystem on Pannikiang Island - Andi Nur Samsi; Rusmidin Rusmidin (Postgraduate, University of Mataram, 2024)
Terebralia palustris is a snail that lives in the mangrove ecosystem. This needs to be done considering that the condition factor (Ponderal Index) and size structure can be a reference for snail management later. Research on the condition factor (Ponderal Index) has never been studied. This research was conducted from August 2018 to July 2019 on Pannikiang Island. Sampling in December 2018 and January 2019 was not performed for weather reasons. The research stations were A and B. Sampling used one large plot measuring 100 m2, and inside, it contained four small plots measuring 0.25 m2 (0.5 m x 0.5 m), which were placed randomly. Data analysis used regression. The condition factor was calculated based on the growth pattern of the total length and weight of the snail's body. The measurement results obtained ten size groups in males and 11 in females. The length (SL) and weight (W) in female snails were more significant than in males. The test results showed that each month of observation showed negative allometry. The snail condition factor fluctuated.